Testing the Financial Convergence Hypothesis and Estimating the Convergence Rate in Selected Countries (Generalized Method of Moments Approach) - Hatef Hazeri Niri; Farzad Rahimzadeh; Siamak ShokouhiFard (پژوهش‌های برنامه و توسعه)
The hypothesis of financial convergence, as one of the upshots of neoclassical economic growth models, emphasizes the process of reducing the financial gap between countries, and in meantime, the speed of this convergence is of particular importance. Hence, the main purpose of this study is to test the financial convergence hypothesis, and to estimate the convergence rate using the dynamic panel technique in selected countries (separately for developed countries (38 countries) and developing countries (34 countries)) based on the generalized torque method (GMM) for the period 1992-2020. According to two models (the ratio of domestic credit to the private sector (percentage of GDP) and the ratio of working capital to GDP in the whole sample and group of developing and developed countries), the results implies the financial convergence in these countries. Also, the convergence rate in the first model is higher in developing countries than in developed countries. However, this speed is relatively higher in the second index of financial deepening (the ratio of money supply to GDP) ,and is adjusted in each period to a greater extent than short-term imbalances to achieve long-term equilibrium.